Lymph Node Metastasis in the Prognosis of Gastroenteropancreatic Neuroendocrine Tumors. Issue 9 (October 2017) - Martin, Jacob A.; Warner, Richard R.P.; Aronson, Anne; Wisnivesky, Juan P.; Kim, Michelle Kang
Abstract : Objectives: This study aimed to determine the prognostic use of the extent of lymph node (LN) involvement in patients with gastroenteropancreatic neuroendocrine tumors (GEP-NETs) by analyzing population-based data. Methods: Patients in the Surveillance, Epidemiology, and End Results registry were identified with histologically confirmed, surgically resected GEP-NETs. We divided patients into 3 lymph node ratio (LNR) groups based on the ratio of positive LNs to total LNs examined: 0.2 or less, greater than 0.2 to 0.5, and greater than 0.5. Disease-specific survival was compared according to LNR group. Results: We identified 3133 patients with surgically resected GEP-NETs. Primary sites included the stomach (11% of the total), pancreas (30%), colon (32%), appendix (20%), and rectum (7%). Survival was worse in patients with LNRs of 0.2 or less (hazard ratio [HR], 1.5; 95% confidence interval [CI], 1.2–2.0), greater than 0.2 to 0.5 (HR, 2.0; 95% CI, 1.6–2.5), and greater than 0.5 (HR, 3.1; 95% CI, 2.5–3.9) compared with N0 patients. Ten-year disease-specific survival decreased as LNR increased from N0 (81%) to 0.2 or less (69%), greater than 0.2 to 0.5 (55%), and greater than 0.5 (50%). Results were consistent for patients with both low- and high-grade tumors from most primary sites. Conclusions: Degree of LN involvement is a prognostic factor at the most common GEP-NET sites. Higher LNR is associated with decreased survival.